La responsabilidad de proteger y el derecho internacional público: consideraciones sobre la licitud del uso de la fuerza por motivos humanitarios ante la falta de autorización del Consejo de Seguridad de la ONU - Pacheco de Freitas, José A. (2015)
The Responsibility to Protect has been presented as a new doctrine —a less aggressive version of humanitarian intervention— that would help the international community face the grave humanitarian crises and the massive human rights violations of the last three decades. However, there is a conflict between the general prohibition of the use of force and the new doctrine when the latter is applied without UN Security Council authorisation. This article analyses the scope and pertinence of the Responsibility to Protect, concluding that it must be understood within the frame of the UN Charter and the general prohibition of the use of force. The strengthening of both the Security Council and the relevant international regimes seems to be the best way to deal with such crises, where as according to current international public law a new exception to the general prohibition —such as the Responsibility to Protect— does not seem to be either a proper or a lawful option.